Dependence of acoustic property on Al substitution for Ca3Ta(Ga1−xAlx)3Si2O14 single crystals. (10th June 2016) - Ohashi, Yuji; Arakawa, Mototaka; Kudo, Tetsuo; Yokota, Yuui; Shoji, Yasuhiro; Kurosawa, Shunsuke; Kamada, Kei; Kushibiki, Jun-ichi; Yoshikawa, Akira
Abstract: The acoustic properties of Ca3 Ta(Ga1− x Al x )3 Si2 O14 (CTGAS x ) were experimentally studied as a function of the Al substitution content x in the ranges from x = 0 to 0.50. Five specimens, X -, Y -, Z -, 35° Y -, and 140° Y -cut, were prepared from each crystal of CTGAS x ( x = 0, 0.25, and 0.50) grown by the Czochralski technique. Longitudinal wave and shear wave velocities for CTGAS x linearly increase with Al content for all propagation directions. Dielectric constants and density were measured and then elastic and piezoelectric constants were determined from the measured velocities for each crystal. The results revealed that all of the constants change linearly with Al content. From the relationship, the constants for CTAS ( x = 1) were estimated. Calculations of the velocities using the determined constants also suggested that the maximum electromechanical coupling factor k 2 for the slow shear wave mode propagating along the rotated Y -axis direction of CTAS was improved to 4.42% compared with 3.83% for CTGS, owing to the Al substitution effect.